Pediatric liver transplantation from a living donor in mitochondrial disease: Good outcomes in DGUOK deficiency?. (22nd April 2020) - Hassan, Shahzeb; Mahmoud, Ali; Mohammed, Taha Osman; Mohammad, Saeed
Abstract: DGUOK deficiency is an autosomal recessive mitochondrial disorder characterized by hepatic and neurological manifestations. In patients with liver failure, the decision to perform LT can be difficult due to the likelihood of progressive neurological disease. We present a case of a 9‐month‐old boy who had DGUOK deficiency (E227K/R118H genotype) intact neurological status and liver failure. His MRI indicated extensive white matter changes, which created hesitation to perform LT. After a multidisciplinary evaluation, he underwent LT from a living donor at 11 months of age. Six years post‐transplant, he has had no significant complications and no progression of neurological symptoms. Our case supports that even in the presence of neurological MRI findings, but in the absence of significant neurological symptoms, LT represents a viable option in DGUOK‐deficient patients who have the E227K/R118H mutation combination along with liver failure.